2020
DOI: 10.3390/ijerph17145208
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Emotional Labor Factors and Working Environment on the Risk of Depression in Pink-Collar Workers

Abstract: Analyzing men and women separately, we examined the associations between six key elements of the psychosocial work environment of pink-collar workers (n = 7633) and the risk of depression, using logistic regression analysis with data from the Fifth Korean Working Conditions Survey (KWCS) conducted in 2017. We assessed the risk of depression according to the presence of emotional display rules (EDR), health and safety information (HSI), and emotional labor. In males, the risk of depression increased when there … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
0
1

Year Published

2020
2020
2025
2025

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 53 publications
2
18
0
1
Order By: Relevance
“…This study found a relationship between ED and mental health outcomes after considering several covariates, but we could not identify the variables in which ED was involved in the pathway and/or mechanism leading to destress, DS, DE, and SI. In the relationship between ED and mental health outcomes, the indirect effects of anger suppression and anger rumination have been reported [ 32 ], and the work environment interactions, such as emotional display rules, angry customers, and health and safety information, have also been reported [ 33 ]. Burnout, a known consequence of ED, showed a negative relationship with emotional intelligence [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…This study found a relationship between ED and mental health outcomes after considering several covariates, but we could not identify the variables in which ED was involved in the pathway and/or mechanism leading to destress, DS, DE, and SI. In the relationship between ED and mental health outcomes, the indirect effects of anger suppression and anger rumination have been reported [ 32 ], and the work environment interactions, such as emotional display rules, angry customers, and health and safety information, have also been reported [ 33 ]. Burnout, a known consequence of ED, showed a negative relationship with emotional intelligence [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…First, they may raise a misclassification bias because the information on the occupation could not fully obtain specific workplace exposure. However, as there are typical workplace exposures for each job type (e.g., non-intellectual demand, low income, and neurotoxic materials at work in blue-collar [ 4 , 36 , 37 ]; bullying from aggressive customers and emotional fatigue, and mental illness in pink-collar [ 38 ]), this study defined the occupational type as approximate workplace exposure. Further studies need to demonstrate the specific occupational exposures that affect cognitive deficits in later life.…”
Section: Discussionmentioning
confidence: 99%
“…The occupational history dataset included profession-related details over the lifetime, right from the participants’ first job in life: Calendar period at hire, calendar period at the exit for each job, and calendar time for unemployment. Occupation generally presents workplace exposure [ 4 , 36 , 37 , 38 ] and the longest-held occupation reflects the worker’s accumulated lifetime working conditions and work-related risk exposures [ 21 ]. Longest-held occupation in a lifetime was determined by the occupation in which an individual was employed for the longest duration in adulthood.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this process, hiding one’s feelings is an emotional regulation process [ 3 ] that affects a range of outcomes such as burnout [ 4 ], depressive mood [ 5 ], and mental health [ 6 , 7 ]. Two previous Korean studies have reported the combined effects of handling angry clients and hiding one’s feelings of depression or anxiety, with some moderation by other job features [ 8 , 9 ]. The detrimental effects of emotional demands on employee well-being [ 10 ] negatively affected work engagement, including vitality at work [ 11 ].…”
Section: Introductionmentioning
confidence: 99%